High-Performance Flexible Electrochemical Heavy Metal Sensor Based on Layer-by-Layer Assembly of Ti3C2Tx/MWNTs Nanocomposites for Noninvasive Detection of Copper and Zinc Ions in Human Biofluids - Hui, Xue; Sharifuzzaman, Md; Sharma, Sudeep; Xuan, Xing; Zhang, Shipeng; Ko, Seok Gyu; Yoon, Sang Hyuk; Park, Jae Yeong (ACS applied materials & interfaces, 2020)
A flexible electrochemical heavy metal sensor based on a gold (Au) electrode modified with layer-by-layer (LBL) assembly of titanium carbide (Ti3C2Tx) and multiwalled carbon nanotubes (MWNTs) nanocomposites was successfully fabricated for the detection of copper (Cu) and zinc (Zn) ions. An LBL drop-coating process was adopted to modify the surface of Au electrodes with Ti3C2Tx/MWNTs treated via ultrasonication to fabricate this novel nanocomposite electrode. In addition, an in situ simultaneous deposition of "green metal" antimony (Sb) and target analytes was performed to improve the detection performance further. The electrochemical measurement was realized using square wave anodic stripping voltammetry (SWASV). Moreover, the fabricated sensor exhibited excellent detection performance under the optimal experimental conditions. The detection limits for Cu and Zn are as low as 0.1 and 1.5 ppb, respectively. Furthermore, Cu and Zn ions were successfully detected in biofluids, that is, urine and sweat, in a wide range of concentration (urine Cu: 10-500 ppb; urine Zn: 200-600 ppb; sweat Cu: 300-1500 ppb; and sweat Zn: 500-1500 ppb). The fabricated flexible sensor also possesses other advantages of ultra-repeatability and excellent stability. Thus, these advantages provide a great possibility for the noninvasive smart monitoring of heavy metals in the future.A flexible electrochemical heavy metal sensor based on a gold (Au) electrode modified with layer-by-layer (LBL) assembly of titanium carbide (Ti3C2Tx) and multiwalled carbon nanotubes (MWNTs) nanocomposites was successfully fabricated for the detection of copper (Cu) and zinc (Zn) ions. An LBL drop-coating process was adopted to modify the surface of Au electrodes with Ti3C2Tx/MWNTs treated via ultrasonication to fabricate this novel nanocomposite electrode. In addition, an in situ simultaneous deposition of "green metal" antimony (Sb) and target analytes was performed to improve the detection performance further. The electrochemical measurement was realized using square wave anodic stripping voltammetry (SWASV). Moreover, the fabricated sensor exhibited excellent detection performance under the optimal experimental conditions. The detection limits for Cu and Zn are as low as 0.1 and 1.5 ppb, respectively. Furthermore, Cu and Zn ions were successfully detected in biofluids, that is, urine and sweat, in a wide range of concentration (urine Cu: 10-500 ppb; urine Zn: 200-600 ppb; sweat Cu: 300-1500 ppb; and sweat Zn: 500-1500 ppb). The fabricated flexible sensor also possesses other advantages of ultra-repeatability and excellent stability. Thus, these advantages provide a great possibility for the noninvasive smart monitoring of heavy metals in the future.